2012
DOI: 10.12707/riii11148
|View full text |Cite
|
Sign up to set email alerts
|

A esperança da pessoa com cancro – estudo em contexto de quimioterapia

Abstract: Contexto: a esperança é um conceito que ajuda a pessoa a lidar com a crise de uma forma mais eficaz. A evidência científica evoca a sua importância no âmbito dos cuidados paliativos, defendendo que esperanças realistas ajudam a pessoa a viver o tempo que resta da melhor forma possível. Objetivos: analisar o índice de esperança de uma amostra de doentes submetidos a quimioterapia e compreender a influência de algumas variáveis sociodemográficas, clínicas e religiosas sobre o mesmo. Metodologia: estudo observaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 5 publications
1
7
0
12
Order By: Relevance
“…The study revealed that those who believed in a higher entity and not had any doubts about his existence had less fear of the future. These data confirm those obtained by other authors and show that religious and spiritual beliefs are closely associated with the concept of quality of life, helping the person to maintain hope, and dealing with the uncertainty of the future in a more effective way [2022]. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study revealed that those who believed in a higher entity and not had any doubts about his existence had less fear of the future. These data confirm those obtained by other authors and show that religious and spiritual beliefs are closely associated with the concept of quality of life, helping the person to maintain hope, and dealing with the uncertainty of the future in a more effective way [2022]. …”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the nationality of the participants in the study may have influenced the results. Generally, the Portuguese are seen as optimistic people, who tend to face the future with hope, as suggested in previous studies [20, 21, 25]. For practical reasons, the study was limited to patients who carry out chemotherapy in day hospital.…”
Section: Discussionmentioning
confidence: 99%
“…E neste sentido, Dias & Ribeiro (2014) dizemnos, que o Enfermeiro é o pro ssional de saúde privilegiado pela proximidade de relação com o doente quer em meio hospitalar quer nas UCCI, e por isso deve estar alertado e sensibilizado para o despiste de sinais de desesperança. Também Pinto (2012), defende que o enfermeiro, poderá ser uma peça fundamental na promoção da esperança, ajudando a pessoa a melhorar as crenças que tem nas suas capacidades através de intervenções que se podem revelar muito úteis, nomeadamente: evitar esconder ou disfarçar a verdade, ajudar o doente a estabelecer objetivos realistas, apoiar a revisão de vida e valorizar as conquistas obtidas, envolver a pessoa ativamente nos cuidados e orientar a família na promoção de fatores encorajantes. Perante a complexidade situacional envolvente dos doentes em UCCI, torna-se fundamental que os prossionais de saúde desenvolvam interesse e compreensão acerca da relação entre a esperança e o sentido de vida, uma vez que ambos proporcionam coragem e um estado de "imunidade" que se vai focalizar num futuro com legitimas possibilidades, ainda que nalguns casos breve.…”
Section: Resumen "A Esperanza En Doentes Internados En Unidades De Cuunclassified
“…The aging process is related to major biological, psychological and social changes together with the prevalence of chronic degenerative diseases that rises from 60 years, highlighting systemic arterial hypertension (SAH), cardiovascular diseases, diabetes mellitus and Osteoarticular diseases (3) . In this sense, it is valid to keep hope against any perceived or imbalanced performance, since it is known that hope affects the health/disease binomial in a positive way, helping the person to face the uncertainties of the future in a more effective and with satisfactory result (5) . Therefore, considering the need for evaluation and classification of the elderly, it is the intention of this study to evaluate the level of hope of the elderly of a University Open to the Third Age, as well as to outline the profile of these elderly people in relation to the socioeconomic variables, characterization of health and Social risks, seeking to highlight the need for actions aimed at public policies that are concrete and satisfactory to the demand of this population, contributing to the understanding of the importance of performing practices related to the promotion of healthy aging.…”
Section: Introductionmentioning
confidence: 99%